Proposição de um método de elaboração e análise de projetos para combate a incêndio com auxílio de ferramentas BIM - Vieira, Bianca Maria Pacheco (2024)
The process of analyzing firefighting projects is carried out by the state Military Fire Brigade and is often a bureaucratic and time-consuming process. Both in the elaboration and in the analysis of the projects, there are difficulties to represent and dimension the safety and fire fighting measures. It is important, then, that these difficulties are identified and worked on to make the projects easier to elaborate, to represent and to analyze, in addition to being more complete in information. Therefore, Building Information Modeling (BIM) can be used as a tool to facilitate, standardize and streamline this process. Its tools and uses such as the creation of templates that standardize the preparation of projects through legends, notes, details, tables and standard boards can bring improvements to the process of firefighting projects. Therefore, this work aims, through the scientific method of Design Science Research (DSR), to propose a method of analysis and elaboration of fire fighting projects with the help of BIM tools, making the process faster and flawless. The work has five stages:(1) Problem awareness stage, in which the current process of analysis and design of projects was mapped, the main difficulties of analysts and designers were found, as well as the main requirements of norms that cause disapproval of projects submitted to CBM-CE analysis; (2) Suggestion Stage, where potential uses and BIM tools were identified and the elaboration of an artifact was proposed to mitigate the problems found in stage 1; (3) Artifact Development Stage, where the evidence found in the previous stages helped in the construction of the design method for designers and analysts in BIM models using a Revit software template; (4) Evaluation Stage, to evaluate the tool in use and its contributions; and, finally, (5) Conclusion Stage, to report the lessons learned in the study, showing how the research objectives were achieved, and indicating what the limitations were. Therefore, as contributions, a method of elaboration and analysis of fire fighting projects was obtained with the aid of BIM tools (standardized template and instructions for use of the template) that meet the highest requirements of the main state (Ceará) and national standards. It is expected that the proposed artifact will speed up the project verification process by PCI designers and CBM-CE analysts, which will reduce the current failure rate.